The Choice between Dividend and Share Repurchase - Mohamad, Jais (World Scientific Publishing Co Pte Ltd, 2011)
This paper examines the payout channel choice of listed firms in KLSE, paying particular attention to why some firms prefer to increase dividends while others prefer to repurchase only. The results indicate that higher prior income, more variability of prior income, and a higher level of retained earnings increase the likelihood that the firms will choose to pay out earnings through dividends. The analysis further indicates that some firms substitute repurchases for dividends.